A framework for food distribution guided by a spatial index of food insecurity - Dawood, Mohammud Fuzail (Stellenbosch : Stellenbosch University, 2025)
Dawood, M. F. 2025. A framework for food distribution guided by a spatial index of food insecurity. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/d93397a5-89a6-4c34-81d1-f00d50e21cf1